The Empowerment of Majelis Taklim In Developing Independence of Household Economy in the Community of Kampung Nelayan Sejahtera of Bengkulu City - Asnaini, Asnaini; Arisandy, Yosy; Eenfryanti, Yunida (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
This paper is aimed at providing a communication forum for the community of Kampung Nelayan Sejahtera of Bengkulu City. The effective and conducive interactions occur among the citizens in overcoming household economic problems, making a mapping of the family economic potential, and providing assistance that supports the development of the family economy according to the potential mapping results. This research uses transformative research methodology. The research reveals that the Majelis Taklim (Islamic Study Forum) of household in Kampung Nelayan Sejahtera, the Prosperous Fishermen Village, has begun to be active again with new targets on family economic empowerment in the field of entrepreneurs. The results of the map of the economic potential of the community's family shows that 2.94% of Muslim households in the Kampung Nelayan Sejahtera live in a prosperous condition (quadrant I), 30.39% in materially poor conditions, (quadrant II), and 14.71% of the observed households were in quadrant III (poor spiritual) and 51.96% are in quadrant IV (absolute poor). This means that the mapping of poor households in such village is in absolute poverty (materially and spiritually poor). Therefore, the focus of empowerment is on revamping material and spiritual abilities through the Majelis Taklim. Tulisan ini bertujuan untuk memberdayakan forum komunikasi bagi masyarakat Kampung Nelayan Sejahtera Kota Bengkulu. Interaksi yang efektif dan kondusif terjadi di antara warga dalam mengatasi masalah ekonomi rumah tangga, membuat pemetaan potensi ekonomi keluarga, dan memberikan bantuan yang mendukung pengembangan ekonomi keluarga sesuai dengan hasil pemetaan potensi. Penelitian ini menggunakan metodologi penelitian transformatif. Penelitian ini mengungkapkan bahwa Majelis Taklim (Forum Pengkajian Islam) rumah tangga di Kampung Nelayan Sejahtera sudah mulai aktif kembali dengan target baru pemberdayaan ekonomi keluarga di bidang wirausaha. Hasil peta potensi ekonomi keluarga masyarakat menunjukkan bahwa 2,94% rumah tangga Muslim di Kampung Nelayan Sejahtera hidup dalam kondisi sejahtera (kuadran I), 30,39% dalam kondisi miskin material, (kuadran II), dan 14,71 % rumah tangga yang diamati berada di kuadran III (spiritual buruk) dan 51,96% berada di kuadran IV (sangat miskin). Ini berarti bahwa pemetaan rumah tangga miskin di desa seperti itu berada dalam kemiskinan absolut (miskin secara material dan spiritual). Karena itu, fokus pemberdayaan adalah pada pembenahan kemampuan material dan spiritual melalui Majelis Taklim.